Behavior of Reinforced Concrete Columns with Double Restraints: a Literature Review and Numerical Simulation Study - Adventino Dwi Kurniawan; Ade Lisantono (Interdisciplinary Social Studies, 2025)
This study investigates the effect of a double-layered restraint system on the axial capacity and deformation behavior of reinforced concrete columns using the Finite Element Method (FEM) approach. It is motivated by the limited effectiveness of single restraints in increasing the ductility and post-peak capacity of columns, necessitating a more efficient restraint configuration. A three-dimensional numerical model was developed in Abaqus/CAE, referencing the experimental specimens of Kumar et al. (2019), which included unconfined, single-confined, and double-confined columns. The model assumed perfect concrete-steel bonding. Validation was conducted by comparing the peak capacity from the simulation results with experimental data to ensure model reliability. Parametric analysis then assessed the effects of inner stirrup geometry, spacing between confinement layers, longitudinal reinforcement ratio, concrete quality, and stirrup spacing on effective confining pressure and axial capacity. The results show that the double restraint system consistently increases effective confining pressure and axial capacity, particularly in configurations with small proximity ratios and high volumetric reinforcement ratios. Compressive capacity predictions using the average effective confining pressure approach (Wu et al., 2016) and the Mander et al. (1988) model agreed well with the FEM results. This study confirms that the double-layered confinement configuration provides significant improvements in the strength and deformation performance of RC columns under monotonic axial loading.